MORPHOLOGICAL ANALYSIS OF THE APEXES OF UPPER MOLARS: A STUDY BY DIGITAL MICROSCOPY - Guimarães Sampaio Trajano Dos Santos, Pedro; Gonçalves Duarte, Marvin; Cavalcanti de Lima Félix, Lucas; Alcantara Eiras Silva , Irene; Dias de Oliveira Antonino, Manoel Arthur; Scavuzzi Carneiro Cunha, Rodolfo; de Queiroz Marques Filho, Eudoro; Reis de Melo Júnior, Paulo Maurício; Coelho de Ataíde Filho, Ailton; Barreto Silva, Luciano (Brazilian Journal of Implantology and Health Sciences, 2025)
Objective: This observational study aims to describe the morphology of maxillary molar apices, emphasizing the variability of shapes, including apical deltas and foramina, using a 1600x HD USB digital microscope. Methodology: Maxillary first molars extracted for orthodontic or periodontal reasons were analyzed. The teeth were cleaned and stored in saline solution until analysis. A 1600x HD USB digital microscope, connected to a computer, was used to capture images of the root apices. The images were examined for the presence of the main foramen, satellite foramina, and other anatomical variations. Results: The analyzed images revealed significant morphological variability of the maxillary molar apices. The apical foramen frequently presented lateral deviations, and multiple foramina were identified around the main foramen, indicating the presence of apical deltas. Illustrative figures present these findings. Conclusion: The morphology of the apices of maxillary molars presents significant variability, including multiple foramina and deviations of the main foramen. The use of 1600x HD USB digital microscopy proved to be an efficient tool for identifying these variations, providing support for more accurate diagnoses and more effective endodontic treatments.